A middle Jurassic abelisaurid from Patagonia and the early diversification of theropod dinosaurs - Pol, Diego (2012)
Abelisaurids are a clade of large, bizarre predatory dinosaurs, most notable for their high, short skulls and extremely reduced forelimbs. They were common in Gondwana during the Cretaceous, but exceedingly rare in the Northern Hemisphere. The oldest definitive abelisaurids so far come from the late Early Cretaceous of South America and Africa, and the early evolutionary history of the clade is still poorly known. Here, we report a new abelisaurid from the Middle Jurassic of Patagonia, Eoabelisaurus mefi gen. et sp. nov., which predates the so far oldest known secure member of this lineage by more than 40 Myr. The almost complete skeleton reveals the earliest evolutionary stages of the distinctive features of abelisaurids, such as the modification of the forelimb, which started with a reduction of the distal elements. The find underlines the explosive radiation of theropod dinosaurs in the Middle Jurassic and indicates an unexpected diversity of ceratosaurs at that time. The apparent endemism of abelisauroids to southern Gondwana during Pangean times might be due to the presence of a large, central Gondwanan desert. This indicates that, apart from continent-scale geography, aspects such as regional geography and climate are important to reconstruct the biogeographical history of Mesozoic vertebrates.